Aramaic bowl spells : Jewish Babylonian Aramaic bowls. Volume one - Shaked, Shaul. (Magical and Religious Literature of Late Antiquity, 2013)
The corpus of Aramaic incantation bowls from Sasanian Mesopotamia is perhaps the most important source we have for studying the everyday beliefs and practices of the Jewish, Christian, Mandaean, Manichaean, Zoroastrian and Pagan communities on the eve of the Islamic conquests. The bowls are from the Schøyen Collection, which has some 650 texts in different varieties of Aramaic: Jewish Aramaic, Mandaic and Syriac, and forms the largest collection of its kind anywhere in the world. This volume presents editions of sixty-four Jewish Aramaic incantation bowls, with accompanying introductions, translations, philological notes, photographs and indices. The themes covered include the magical divorce and the accounts of the wonder-working sages Ḥanina ben Dosa and Joshua bar Peraḥia. It is the first of a multi-volume project that aims to publish the entire Schøyen Collection of Aramaic incantation bowls.